Strategi Fundrasing Wakaf Di Badan Wakaf Pondok Pesantren Mawaridussalam - M Guffar Harahap (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2019)
Waqf is one of the teachings that is very noticed in Islam and has socio-economic value for the welfare of society. The principle of property ownership in Islam states that property is not justified by a group of people. Along with the development of the waqf era it is now in the form of productive money and endowments. With this development the government also expanded the waqf property, one of which was money waqf as stated in Government Regulation No.42 of 2006. However, among the reality of the understanding of the development of waqf this was not widely known by the public. In general, people understand waqf more traditionally both from harmony, the terms and purpose of holding waqf itself. Like the distribution of waqf for the sake of worship. In addition, the level of expertise and knowledge of waqf nadzir as the main actors in waqf fundraising to the community has not been maximally developed for waqf fundraising strategies to attract the waqf, among others, just waiting for the waqif candidates to endow their assets. If this condition is not addressed, it can result in waqf not being optimal and developing. Based on this, it does not cover the possibility of waqf boarding schools to anticipate this. This study aims to find out about waqf fundraising strategies in mawaridussalam Islamic boarding schools and their impact. The research methods used were observation, interviews, SWOT analysis with a qualitative approach. The results of the study showed that fundraising strategies were used by waqf institutions of mawaridussalam islamic boarding school, namely annual events (building community trust), socialization of santri to their families, stocking up, endowments and waqf coaching.